Projeto da estrutura de um VANT: Design criado por otimização topológica e fabricação por Fused Deposition Modeling-FDM - Silva, Luis Felipe Alexandre da (Universidade Federal Rural do Semi-Árido, 2021)
Topological optimization is a method used to create designs that can be used in the development of structural designs, helping to find lightweight and efficient geometry. The design creation process happens through an algorithm, this type of practice is known as generative design. However, the resulting geometries from topological optimization are generally complex, which makes fabrication unfeasible by conventional manufacturing processes. On the other hand, additive manufacturing processes stand out for their ease in manufacturing highly complex geometries. Therefore, the objective of the present work is to develop a structure by the topological optimization method, and to simulate its fabrication by additive manufacturing, focusing on the FDM process (Melting and Deposition Modeling). The developed project was of the structure of a UAV (Unmanned Aerial Vehicle) of the quadricopter type; this type of vehicle is sensitive to reducing the weight of the structure, as any savings in structural load are directly translated into useful load capacity and increased autonomy. In addition, the project aims to be affordable to manufacture, for this, the structure is mountable, so that each part can be manufactured in a low-cost printer. To guide the development of the structure, studies were focused on understanding good design practices, applying them as best as possible to topological optimization and manufacturing by additive manufacturing. Finally, the result obtained was a PLA (Lactic Acid Poly) structure made of FDM, which can be compared to the F650 drone (commercial, made of carbon fiber).
Keywords: Otimização topológica; Manufatura aditiva; VANT; ENGENHARIAS::ENGENHARIA MECANICA